1982
DOI: 10.7326/0003-4819-96-2-133
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Doxorubicin Cardiotoxicity by Prolonged Continuous Intravenous Infusion

Abstract: Doxorubicin (Adriamycin) was administered by continuous infusion to reduce peak plasma levels and thus lessen cardiac toxicity. Cardiotoxicity was monitored by noninvasive methods, and endomyocardial biopsy specimens were studied by electronmicroscopy. Cardiotoxicity was compared in 21 patients receiving doxorubicin intravenously over 48 or 96 hours and in 30 control patients treated by standard intravenous injection. Both groups were studied prospectively and were well matched by risk factors for doxorubicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
199
0
18

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(219 citation statements)
references
References 11 publications
2
199
0
18
Order By: Relevance
“…11 In a prospective phase II study of infusional etoposide, vincristine, and doxorubicin (EPOCH regimen) in recurrent and resistant lymphomas, no clinically significant cardiac toxicity was observed, despite that 94% of patients had previously received an anthracycline-containing regimen. 12 However, pharmacokinetic analyses of long-term continuousinfusion doxorubicin have shown, particularly for older patients, significant interpatient variations in steady-state plasma concentrations and have suggested an individual patient dose adjustment based on hematopoietic nadir.…”
mentioning
confidence: 99%
“…11 In a prospective phase II study of infusional etoposide, vincristine, and doxorubicin (EPOCH regimen) in recurrent and resistant lymphomas, no clinically significant cardiac toxicity was observed, despite that 94% of patients had previously received an anthracycline-containing regimen. 12 However, pharmacokinetic analyses of long-term continuousinfusion doxorubicin have shown, particularly for older patients, significant interpatient variations in steady-state plasma concentrations and have suggested an individual patient dose adjustment based on hematopoietic nadir.…”
mentioning
confidence: 99%
“…1 Legha et al studied continuousinfusion doxorubicin and found that endomyocardial biopsy changes were significantly less severe than in patients receiving bolus infusion. 12 Reduction of the cardiotoxic profile of the anthracycline itself continues to be of interest. Epirubicin reportedly had lower cardiotoxicity compared with doxorubicin on the basis of a mg/m 2 cumulative dose.…”
Section: Discussionmentioning
confidence: 99%
“…Densification of FEC 100 from 3-weekly to 2-weekly with G-CSF support has, however, been found unfeasible as a result of high toxicity, including pericardial effusion, pneumonitis and frequent hospitalisations [19,20]. Decreasing peak plasma levels of doxorubicin by continuous infusion has also been shown to reduce cardiotoxicity [21]. Dose densification of Doc therapy is feasible, as demonstrated in a study of biweekly doxorubicin 50 mg/m 2 and Doc 75 mg/m 2 [22].…”
Section: Introductionmentioning
confidence: 99%